A discussion with Friedrich von Hayek - Friedrich von Hayek (Washington D.C. American Enterprise Institute for Public Policy Research, 1975)
"A Discussion with Friedrich A. von Hayek" presents the views of one of the world's most distinguished economists on the timely topics of inflation, unemployment, and economic policy.
Held at the American Enterprise Institute on April 9, 1975.
rpm 14/02/2019
Loans
Keywords: Hayek, Friedrich A. von, -- 1899-1992.; Hayek, Friedrich August von; Unemployment; Inflation; Economic Policy